Implementation Plan in Response to the Board-Endorsed Recommendations for the IEO Evaluation of IMF Forecasts : Process, Quality, and Country Perspective. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2015)
This paper sets out Management's response to the Independent Evaluation Office's (IEO) evaluation of IMF Forecasts: Process, Quality, and Country Perspectives. The implementation plan proposes specific actions to address the five recommendations that received broad support from the Executive Board, namely (i) maintaining the practice of commissioning external evaluations of IMF forecasts, (ii) enhancing the processes and incentives for learning from past forecast performance, (iii) extending guidance to desk economists on forecasting methodologies, (iv) publishing a description of the WEO forecasting process, and (iv) improving the public availability of data related to forecasts and outturns. Several of the proposed actions to address the Board-endorsed IEO recommendations have already been implemented following the Board discussion, while the implementation of some other actions is underway. This paper also explains how implementation will be monitored.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Country Desk; Country; Desk Economist; IEO Evaluation; PP